The father image and marriage partner image for girls from single-parent families - Філоненко, Любов Миколаївна; Терещенко, Надія Миколаївна (Psychological Counseling and Psychotherapy, 1970)
This article explores the features of influence of the father image on the marriage partner image in girls from single-parent families. The study involved 20 unmarried girls from single-parent families and 20 girls from complete families. Differences were found in the perception of marriage and family values among girls of complete and incomplete families. 4 factors were obtained that reflect the nature of the influence of a father's image on the image of a marriage partner: a masculine father, feminine father , androgynous father, dependent / independent father.